Google Classroom Interactive in Project-based Learning Model Accompanied by Formative Assessments to Improve Understanding of Dynamic Fluid Concepts - Vriesnando Haris Banyunegoro; Khusaini Khusaini; Arif Hidayat; Febi Putri (Experiment: Journal of Science Education, 2026)
This study aims to create interactive learning media using Google Classroom combined with the Project-based Learning (PjBL) model and formative assessment to improve the understanding of 11th-grade students about fluid dynamics. The method used is Research and Development (R&D) with ADDIE steps, which consist of analysis, design, development, implementation, and evaluation. The results of the evaluation by experts showed that the media was highly valid, with a validity score of 90% from subject matter experts and 91.67% from media experts. A limited trial at SMA Negeri 2 Pare involved two classes: one experimental class that used the media, and one control class that did not use the media. Analysis results showed a significant difference between the learning outcomes of the two groups. The N-Gain calculation indicated a high increase in understanding in the experimental class (74%) and a low increase in the control class (30%). Google Classroom-based interactive media with PjBL and formative assessment has proven valid, practical, and effective in improving understanding of fluid dynamics concepts. Active student involvement in projects, Google Classroom access that can be done anywhere and anytime, and continuous teacher feedback to students are factors in improving understanding of fluid dynamics concepts. The use of this learning strategy is an alternative to support learning in the National Curriculum at the secondary school level.